Finite element study of the efficacy of three different loops for bodily protraction of the mandibular molar - Aditi Mehta; Alap Shah; Anisha Prasad; Bharvi Jani; Kinnari Shah; Anirudh Kulkarni; Nattapon Chantarapanich; Samroeng Inglam; Mohammad Fareed; Anand Marya (Scientific Reports)
Abstract This study aimed to compare three different loops (T loop, Cherry loop, and Open helical loop) and optimal tip back angle (10°, 15°, 20°) for protraction of mandibular second molar using Finite Element Model (FEM). A CBCT scan of a 20-year-old patient was recorded. It was converted into a CAD file and then into a FEM. A FEM model developed was used to find out the efficacy of the loops and optimal tip-back angles. Displacement of the molar was measured at four reference points: the mesio-buccal cusp, distobuccal cusp, mesial root, and the distal root of the first molar. No significant difference was seen in the displacement for all three loops. At a 10° angle, there was more mesial tipping (5.9°) and molar extrusion. At a 15° angle, there was less mesial tipping (2.9-3°) and no changes in the vertical plane. At a 20° angle, there was bodily movement and intrusion of molars. All three loops are equally effective in the protraction of mandibular molar. A 15° tip back angle was most effective in protracting the mandibular molar as only a negligible amount of mesial tipping of the molar was seen, and there was no extrusion or intrusion of the molar, thus maintaining the occlusal plane. Loop mechanics are preferred over the use of power chains as this helps maintain better control over the molar position during protraction. Loops are very effective at avoiding mesial tipping and extrusion of molars during mesialization to close spaces.